Bible the story of the King James Version, 1611-2011 - Campbell, Gordon, 1944- (Oxford ; New York : Oxford University Press, 2010)
This is a history of the King James Version of the Bible (known in Britain as the Authorised Version) over the four hundred years from its remote beginnings to the present day. Gordon Campbell, expert in Renaissance literatures, tells the fascinating and complex story of how this translation came to be commissioned, of who the translators were, and of how the translation was accomplished. The story does not end with the printing of that first edition, but introduces the subsequent generations who edited and interacted with the text.
Includes bibliographical references (p. 314-332) and index.
Keywords: Bible. -- History; Bible. -- Criticism, Textual; Bible -- Translating; Religion; BIBLES / King James Version / General; Electronic books